1999
DOI: 10.1046/j.1440-1819.1999.00613.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of psychotic disorder associated with a right temporal lesion: A special reference to magnetic resonance imaging and single photon emission computed tomography findings

Abstract: A number of studies demonstrated a close association between psychotic symptoms and temporal lobe abnormalities. For example, it is well known that psychosis occurs in association with temporal lobe epilepsy, [1][2][3] and recent studies demonstrate morphological and functional abnormalities in the temporal lobe of schizophrenic brains. [4][5][6][7] In addition, there are some reports demonstrating focal temporal lesions such as stroke, 8 trauma 8 as well as brain tumors 9,10 as a causal lesion for psychotic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…These included delusions based on autobiographical memory failures, place misidentification with double orientation and persecutory delusional beliefs about staff members and their intentions. Similar neuropsychiatric symptoms have been argued, on the basis of case and cohort studies in AD, to arise from regional neuropsychological failures in a context of disturbances in reality monitoring due to right hemisphere dysfunction (Feinberg & Shapiro, 1989;Förstl, Almeida, Owen, Burns, & Howard, 1991;Mizukami, Yamakawa, Yokoyama, Shiraishi, & Kobayashi, 1999;Shanks & Venneri, 2002;Staff et al, 1999). Such symptoms are seen with highest frequency in patients with right frontoparietal dysfunction.…”
Section: Discussionmentioning
confidence: 58%
“…These included delusions based on autobiographical memory failures, place misidentification with double orientation and persecutory delusional beliefs about staff members and their intentions. Similar neuropsychiatric symptoms have been argued, on the basis of case and cohort studies in AD, to arise from regional neuropsychological failures in a context of disturbances in reality monitoring due to right hemisphere dysfunction (Feinberg & Shapiro, 1989;Förstl, Almeida, Owen, Burns, & Howard, 1991;Mizukami, Yamakawa, Yokoyama, Shiraishi, & Kobayashi, 1999;Shanks & Venneri, 2002;Staff et al, 1999). Such symptoms are seen with highest frequency in patients with right frontoparietal dysfunction.…”
Section: Discussionmentioning
confidence: 58%
“…12,13 Also in nonepileptic patients several cases of temporal lobe lesions associated with psychotic symptoms have been described. For example, Ortiz et al 14 described a patient developing psychotic depression having acquired an ischemic left temporal lesion, whereas Mizukami et al 15 reported on a psychotic patient with a right temporal lesion of unknown origin. Blackshaw and Bowen 16 presented a patient with atypical psychosis cooccurring with a left fronto-temporal arachnoidal cyst.…”
Section: Discussionmentioning
confidence: 99%
“…One report described how a focal temporal-lobe tumor expanded to the CPA and caused postoperativepsychotic symptoms 5. However, in cases where psychotic patients show few or no neurological symptoms, magnetic resonance imaging (MRI) can be an extremely useful tool for evaluating organic lesions; this is often overlooked by psychiatrists.…”
Section: Introductionmentioning
confidence: 99%